Meadas sentimentais: afetos singulares entre humanos e um sistema de inteligência artificial antidepressão - Amado, Giselly Tiago Ribeiro (2023)
This study aims to investigate how, in affective-discursive terms, the human-artificial intelligence relationship is constituted within the Replika application, shared on Reddit. For this purpose, the study adopts Spinoza's concept of the immanence of mind and body, considering them as aspects of a single substance in which affections manifest in the human experience. It employs a cartographic approach inspired by Deleuze and Guattari, alongside Bruno Latour's actor-network theory, as a backdrop. The study proposes that interactions and meaning constructions regarding the human-artificial intelligence relationship occur in/through language, deeply influenced by discursive dynamics, it adopts Discourse Analysis, as proposed by Pêcheux, as a theoretical-methodological framework to comprehend how discourses are produced, considering the social, political, cultural, and ideological aspects influencing the production and interpretation of meanings within the discursive practices shared by Replika users on Reddit. This exploration delves into the complexity of interaction, emphasizing Replika's presence as a symbolic object that forms intense emotional connections and the potential for the discourse of various emotions. The analysis suggests that this artificial intelligence can function as a complex affective element, influencing the capacity for action of its users. It emphasizes that affections are not predetermined; rather, they emerge in interaction and are tied to experiences. The relationship developed between the user and Replika is shaped by human parameters, where the user nurtures expectations that this interaction will surpass previously experienced discomforts and challenges. The study proposes that by understanding affections within interactions, there exists the opportunity for self-understanding.